INDONESIAN CONSUMERS’ ATTITUDE TOWARDS NIKE’S MULTICULTURAL CELEBRITY ENDORSEMENT - Liora, Heidy Audelia; Parmono, Vincentius Rachmadi (Program Studi Administrasi Bisnis, FIABIKOM, Unika Atma Jaya, 2023)
With multiculturalism and famous factor that has risen within these last few years, the researcher wanted to explore more about culture background and the significance of it in an endorsement especially within Nike’s international marketing scope. This study discusses the influence of credibility, lack of irritation, informativeness, entertainment, and personalization of the Nike company. This research is a quantitative research, with primary data collection done by distributing questionnaires via Google Forms. Data collected as many as 103 people respondent. Secondary data collection is done by reading, study, and understand several sources of literature, namely books, journals, and articles. The analysis technique used is logistic regression analysis using the JASP application. The results of data analysis in this study show that credibility, lack of irritation, informativeness, entertainment, and personalization show that they are insignificant to the outcome.